Groundwater irrigation: management, adaptation and economic costs under declining resource conditions - Seenath Peedikakandi (Department of Agricultural Economics, College of Horticulture, 2017)
Groundwater is the major source of domestic use and irrigation in Kerala, accounting for 39 per cent of net irrigated area. Irrigated agriculture in the state shows continuous increase over years. At the same time Kerala is reported as third among the states with highest depletion of groundwater. This situation poses challenges in agricultural production. The study ‘Groundwater irrigation: Management, adaptation and economic costs under declining resource conditions’ was undertaken, in this background. The objectives of the study were to analyse the extent of decline in groundwater resources and farmers’ understanding of the same, to analyse the extraction practices, management and economic efficiency of groundwater irrigation and coping (short term) and adaptation (long term) strategies towards management of groundwater decline and the economic cost of adaptation strategies. The study was conducted in Palakkad district of Kerala. Based on the stage of ground water development, three Block Panchayats viz., Chittur (over exploited), Malampuzha (critical) and Pattambi (semi-critical) were selected for the study. 50 Open Well (OW) irrigated and 50 Bore Well (BW) irrigated farms from each BP were randomly selected from the Grama Panchayats (GPs) where observational wells of the GWD (Ground Water Department- Kerala) are situated. Primary data was collected from the sample farms through field visits using pre-tested structured interview schedule and through direct observation. PRA (Participatory Rural Appraisal) was also conducted in each BP to draw the time line of changes in ground water status and social perceptions. Secondary data on monthly water levels of Groundwater Monitoring Wells (GMWs) maintained by GWD (Palakkad),rainfall data and published reports were used for the study. Statistical tools like descriptive analysis, regression and Stochastic Frontier Function were employed for analysis of the data. In most of the GMWs in the study area, the Water Level from Ground (WLG) has been declining over the years. The trend was more predominant during early summer (Dec.–Jan.) in Chittur and Malampuzha and in late summer in Pattambi BP. Regression analysis showed that WLG was significantly influenced by one year lagged rainfall in Chittur and current year rainfall in Malampuzha and Pattambi. The average well density was 205/km2 with highest in Pattambi. Density of defunct wells was highest (45/km2) and the average functional age of bore wells was lowest (7 years) in Chittur. The depth of well was highest in Chittur where bore well depth (136 mbgl- meters below ground level) was double than that of Pattambi. Coconut based cropping system was prevalent in most of the farms except in Malampuzha where paddy was the major crop. Flood, basin and sprinkler irrigations were found to be more common in Malampuzha and Pattambi BPs, while drip irrigation was prevalent in Chittur. Cost of irrigation in Chittur was about Rs. 29,000/ha/year which accounted for 37 per cent of cost of cultivation. Annual net return per ha. of farm was lowest (Rs. 17,640/-) in Chittur due to low cropping intensity. Stochastic Frontier Analysis indicated that mean economic efficiency was high (99.9%) in Chittur as most of the farms were functioning along the cost frontier. The variability among the farms in Chittur was low. Respondents opined that groundwater is declining over the years irrespective of the region. It has been so, for more than a decade in Chittur affecting socio-economic well-being of farmers. They attributed intensive extraction through bore wells and low rainfall as the major reasons for the decline. Farm level adaptations to water scarcity are classified under ‘supply management’ (methods that facilitated increase in quantity of water available for irrigation) and ‘demand management’ (methods that tried to use the water effectively through minimizing the use) strategies. The supply management strategies were mainly exploitative in nature which included digging new bore well (52-58%), improved draft technology with compressor pumps (58%), taking pits for water conservation (7%), coconut husk burial (12%), coconut leaf mulching (18%) and dependence on water markets (8%). Digging new bore well was the most common supply management strategy in Chittur which is highly capital intensive. The average cost amounted to Rs. 8,520/ha/year. Intensive extraction was done by excessive use of subsidized electricity. Adoption of drip irrigation (60%) was the most widely practiced demand management strategy which cost about Rs. 22,000/ha/year. Cropping pattern change from paddy and sugarcane to coconut was also observed. About 18 per cent of the land area in Chittur was kept fallow due to water scarcity. The study brings out results that suggest policy interventions in regulating bore well digging and revisiting the power subsidy system. In Chittur area, where the rainfall is scanty, extension of the Right Bank Canal of the Chittur River irrigation project is the most feasible solution. Taking up on-farm research trials in the area to suggest efficient farming systems and practices may also be done. Simultaneously water resource conservation strategies are to be popularized through awareness creation, capacity building programmes and subsidy support.